Cell adhesion and cell fate: An effective feedback loop during zebrafish gastrulation - Barone, Vanessa
Cell-cell contact formation constitutes the first step in the emergence of multicellularity in evolution, thereby allowing the differentiation of specialized cell types. In metazoan development, cell-cell contact formation is thought to influence cell fate specification, and cell fate specification has been implicated in cell-cell contact formation. However, remarkably little is yet known about whether and how the interaction and feedback between cell-cell contact formation and cell fate specification affect development. Here we identify a positive feedback loop between cell-cell contact duration, morphogen signaling and mesendoderm cell fate specification during zebrafish gastrulation. We show that long lasting cell-cell contacts enhance the competence of prechordal plate (ppl) progenitor cells to respond to Nodal signaling, required for proper ppl cell fate specification. We further show that Nodal signalling romotes ppl cell-cell contact duration, thereby generating an effective positive feedback loop between ppl cell-cell contact duration and cell fate specification. Finally, by using a combination of theoretical modeling and experimentation, we show that this feedback loop determines whether anterior axial mesendoderm cells become ppl progenitors or, instead, turn into endoderm progenitors. Our findings reveal that the gene regulatory networks leading to cell fate diversification within the developing embryo are controlled by the interdependent activities of cell-cell signaling and contact formation.

Model counting for recursively-defined strings - Trinh, Minh; Chu, Duc Hiep; Jaffar, Joxan
We present a new algorithm for model counting of a class of string constraints. In addition to the classic operation of concatenation, our class includes some recursively defined operations such as Kleene closure, and replacement of substrings. Additionally, our class also includes length constraints on the string expressions, which means, by requiring reasoning about numbers, that we face a multi-sorted logic. In the end, our string constraints are motivated by their use in programming for web applications. Our algorithm comprises two novel features: the ability to use a technique of (1) partial derivatives for constraints that are already in a solved form, i.e. a form where its (string) satisfiability is clearly displayed, and (2) non-progression, where cyclic reasoning in the reduction process may be terminated (thus allowing for the algorithm to look elsewhere). Finally, we experimentally compare our model counter with two recent works on model counting of similar constraints, SMC [18] and ABC [5], to demonstrate its superior performance.

Timed network games with clocks - Avni, Guy; Guha, Shibashis; Kupferman, Orna
Network games are widely used as a model for selfish resource-allocation problems. In the classical model, each player selects a path connecting her source and target vertex. The cost of traversing an edge depends on the number of players that traverse it. Thus, it abstracts the fact that different users may use a resource at different times and for different durations, which plays an important role in defining the costs of the users in reality. For example, when transmitting packets in a communication network, routing traffic in a road network, or processing a task in a production system, the traversal of the network involves an inherent delay, and so sharing and congestion of resources crucially depends on time. We study timed network games , which add a time component to network games. Each vertex v in the network is associated with a cost function, mapping the load on v to the price that a player pays for staying in v for one time unit with this load. In addition, each edge has a guard, describing time intervals in which the edge can be traversed, forcing the players to spend time on vertices. Unlike earlier work that add a time component to network games, the time in our model is continuous and cannot be discretized. In particular, players have uncountably many strategies, and a game may have uncountably many pure Nash equilibria. We study properties of timed network games with cost-sharing or congestion cost functions: their stability, equilibrium inefficiency, and complexity. In particular, we show that the answer to the question whether we can restrict attention to boundary strategies, namely ones in which edges are traversed only at the boundaries of guards, is mixed.

The Gibbs free energy of homogeneous nucleation: From atomistic nuclei to the planar limit - Cheng, Bingqing; Tribello, Gareth A.; Ceriotti, Michele (The Journal of Chemical Physics)
In this paper we discuss how the information contained in atomistic simulations of homogeneous nucleation should be used when fitting the parameters in macroscopic nucleation models. We show how the number of solid and liquid atoms in such simulations can be determined unambiguously by using a Gibbs dividing surface and how the free energy as a function of the number of solid atoms in the nucleus can thus be extracted. We then show that the parameters (the chemical potential, the interfacial free energy, and a Tolman correction) of a model based on classical nucleation theory can be fitted using the information contained in these free-energy profiles but that the parameters in such models are highly correlated. This correlation is unfortunate as it ensures that small errors in the computed free energy surface can give rise to large errors in the extrapolated properties of the fitted model. To resolve this problem we thus propose a method for fitting macroscopic nucleation models that uses simulations of planar interfaces and simulations of three-dimensional nuclei in tandem. We show that when the chemical potentials and the interface energy are pinned to their planar-interface values, more precise estimates for the Tolman length are obtained. Extrapolating the free energy profile obtained from small simulation boxes to larger nuclei is thus more reliable.

Bridging the gap between atomistic and macroscopic models of homogeneous nucleation - Cheng, Bingqing; Ceriotti, Michele (The Journal of Chemical Physics)
Macroscopic theories of nucleation such as classical nucleation theory envision that clusters of the bulk stable phase form inside the bulk metastable phase. Molecular dynamics simulations are often used to elucidate nucleation mechanisms, by capturing the microscopic configurations of all the atoms. In this paper, we introduce a thermodynamic model that links macroscopic theories and atomic-scale simulations and thus provide a simple and elegant framework for testing the limits of classical nucleation theory.

Data from: Ret and Etv4 promote directed movements of progenitor cells during renal branching morphogenesis - Riccio, Paul; Cebrián, Christina; Zong, Hui; Hippenmeyer, Simon; Costantini, Frank
Branching morphogenesis of the epithelial ureteric bud forms the renal collecting duct system and is critical for normal nephron number, while low nephron number is implicated in hypertension and renal disease. Ureteric bud growth and branching requires GDNF signaling from the surrounding mesenchyme to cells at the ureteric bud tips, via the Ret receptor tyrosine kinase and coreceptor Gfrα1; Ret signaling up-regulates transcription factors Etv4 and Etv5, which are also critical for branching. Despite extensive knowledge of the genetic control of these events, it is not understood, at the cellular level, how renal branching morphogenesis is achieved or how Ret signaling influences epithelial cell behaviors to promote this process. Analysis of chimeric embryos previously suggested a role for Ret signaling in promoting cell rearrangements in the nephric duct, but this method was unsuited to study individual cell behaviors during ureteric bud branching. Here, we use Mosaic Analysis with Double Markers (MADM), combined with organ culture and time-lapse imaging, to trace the movements and divisions of individual ureteric bud tip cells. We first examine wild-type clones and then Ret or Etv4 mutant/wild-type clones in which the mutant and wild-type sister cells are differentially and heritably marked by green and red fluorescent proteins. We find that, in normal kidneys, most individual tip cells behave as self-renewing progenitors, some of whose progeny remain at the tips while others populate the growing UB trunks. In Ret or Etv4 MADM clones, the wild-type cells generated at a UB tip are much more likely to remain at, or move to, the new tips during branching and elongation, while their Ret−/− or Etv4−/− sister cells tend to lag behind and contribute only to the trunks. By tracking successive mitoses in a cell lineage, we find that Ret signaling has little effect on proliferation, in contrast to its effects on cell movement. Our results show that Ret/Etv4 signaling promotes directed cell movements in the ureteric bud tips, and suggest a model in which these cell movements mediate branching morphogenesis.

Data from: Error-robust modes of the retinal population code - Prentice, Jason; Marre, Olivier; Ioffe, Mark; Loback, Adrianna; Tkačik, Gašper; Berry, Michael
Across the nervous system, certain population spiking patterns are observed far more frequently than others. A hypothesis about this structure is that these collective activity patterns function as population codewords–collective modes–carrying information distinct from that of any single cell. We investigate this phenomenon in recordings of ∼150 retinal ganglion cells, the retina’s output. We develop a novel statistical model that decomposes the population response into modes; it predicts the distribution of spiking activity in the ganglion cell population with high accuracy. We found that the modes represent localized features of the visual stimulus that are distinct from the features represented by single neurons. Modes form clusters of activity states that are readily discriminated from one another. When we repeated the same visual stimulus, we found that the same mode was robustly elicited. These results suggest that retinal ganglion cells’ collective signaling is endowed with a form of error-correcting code–a principle that may hold in brain areas beyond retina.

Transient behavior between multi-cell flow states in ferrofluidic Taylor-Couette flow - Altmeyer, Sebastian; Do, Younghae; Ryu, Soorok (Chaos)
We investigate transient behaviors induced by magnetic fields on the dynamics of the flow of a ferrofluid in the gap between two concentric, independently rotating cylinders. Without applying any magnetic fields, we uncover emergence of flow states constituted by a combination of a localized spiral state (SPIl) in the top and bottom of the annulus and different multi-cell flow states (SPI2v, SPI3v) with toroidally closed vortices in the interior of the bulk (SPIl+2v = SPIl + SPI2v and SPIl+3v = SPIl + SPI3v). However, when a magnetic field is presented, we observe the transient behaviors between multi-cell states passing through two critical thresholds in a strength of an axial (transverse) magnetic field. Before the first critical threshold of a magnetic field strength, multi-stable states with different number of cells could be observed. After the first critical threshold, we find the transient behavior between the three- and two-cell flow states. For more strength of magnetic field or after the second critical threshold, we discover that multi-cell states are disappeared and a localized spiral state remains to be stimulated. The studied transient behavior could be understood by the investigation of various quantities including a modal kinetic energy, a mode amplitude of the radial velocity, wavenumber, angular momentum, and torque. In addition, the emergence of new flow states and the transient behavior between their states in ferrofluidic flows indicate that richer and potentially controllable dynamics through magnetic fields could be possible in ferrofluic flow.

Improved algorithms for parity and Streett objectives - Chatterjee, Krishnendu; Henzinger, Monika H; Loitzenbauer, Veronika (Logical Methods in Computer Science)
The computation of the winning set for parity objectives and for Streett objectives in graphs as well as in game graphs are central problems in computer-aided verification, with application to the verification of closed systems with strong fairness conditions, the verification of open systems, checking interface compatibility, well-formedness of specifications, and the synthesis of reactive systems. We show how to compute the winning set on n vertices for (1) parity-3 (aka one-pair Streett) objectives in game graphs in time O(n5/2) and for (2) k-pair Streett objectives in graphs in time O(n2+nklogn). For both problems this gives faster algorithms for dense graphs and represents the first improvement in asymptotic running time in 15 years.

Edit distance for pushdown automata - Chatterjee, Krishnendu; Henzinger, Thomas A; Ibsen-Jensen, Rasmus; Otop, Jan (Logical Methods in Computer Science)
The edit distance between two words w 1 , w 2 is the minimal number of word operations (letter insertions, deletions, and substitutions) necessary to transform w 1 to w 2 . The edit distance generalizes to languages L 1 , L 2 , where the edit distance from L 1 to L 2 is the minimal number k such that for every word from L 1 there exists a word in L 2 with edit distance at most k . We study the edit distance computation problem between pushdown automata and their subclasses. The problem of computing edit distance to a pushdown automaton is undecidable, and in practice, the interesting question is to compute the edit distance from a pushdown automaton (the implementation, a standard model for programs with recursion) to a regular language (the specification). In this work, we present a complete picture of decidability and complexity for the following problems: (1) deciding whether, for a given threshold k , the edit distance from a pushdown automaton to a finite automaton is at most k , and (2) deciding whether the edit distance from a pushdown automaton to a finite automaton is finite.

Unifying two views on multiple mean-payoff objectives in Markov decision processes - Chatterjee, Krishnendu; Křetínská, Zuzana; Kretinsky, Jan (Logical Methods in Computer Science)
We consider Markov decision processes (MDPs) with multiple limit-average (or mean-payoff) objectives. There exist two different views: (i) the expectation semantics, where the goal is to optimize the expected mean-payoff objective, and (ii) the satisfaction semantics, where the goal is to maximize the probability of runs such that the mean-payoff value stays above a given vector. We consider optimization with respect to both objectives at once, thus unifying the existing semantics. Precisely, the goal is to optimize the expectation while ensuring the satisfaction constraint. Our problem captures the notion of optimization with respect to strategies that are risk-averse (i.e., ensure certain probabilistic guarantee). Our main results are as follows: First, we present algorithms for the decision problems which are always polynomial in the size of the MDP. We also show that an approximation of the Pareto-curve can be computed in time polynomial in the size of the MDP, and the approximation factor, but exponential in the number of dimensions. Second, we present a complete characterization of the strategy complexity (in terms of memory bounds and randomization) required to solve our problem.

Nested weighted automata - Chatterjee, Krishnendu; Henzinger, Thomas A; Otop, Jan (ACM Transactions on Computational Logic (TOCL))
Recently there has been a significant effort to handle quantitative properties in formal verification and synthesis. While weighted automata over finite and infinite words provide a natural and flexible framework to express quantitative properties, perhaps surprisingly, some basic system properties such as average response time cannot be expressed using weighted automata or in any other known decidable formalism. In this work, we introduce nested weighted automata as a natural extension of weighted automata, which makes it possible to express important quantitative properties such as average response time. In nested weighted automata, a master automaton spins off and collects results from weighted slave automata, each of which computes a quantity along a finite portion of an infinite word. Nested weighted automata can be viewed as the quantitative analogue of monitor automata, which are used in runtime verification. We establish an almost-complete decidability picture for the basic decision problems about nested weighted automata and illustrate their applicability in several domains. In particular, nested weighted automata can be used to decide average response time properties.

Water wave packets - Jeschke, Stefan; Wojtan, Christopher J (ACM Transactions on Graphics)
This paper presents a method for simulating water surface waves as a displacement field on a 2D domain. Our method relies on Lagrangian particles that carry packets of water wave energy; each packet carries information about an entire group of wave trains, as opposed to only a single wave crest. Our approach is unconditionally stable and can simulate high resolution geometric details. This approach also presents a straightforward interface for artistic control, because it is essentially a particle system with intuitive parameters like wavelength and amplitude. Our implementation parallelizes well and runs in real time for moderately challenging scenarios.

Faster statistical model checking for unbounded temporal properties - Daca, Przemyslaw; Henzinger, Thomas A; Kretinsky, Jan; Petrov, Tatjana (ACM Transactions on Computational Logic)
We present a new algorithm for the statistical model checking of Markov chains with respect to unbounded temporal properties, including full linear temporal logic. The main idea is that we monitor each simulation run on the fly, in order to detect quickly if a bottom strongly connected component is entered with high probability, in which case the simulation run can be terminated early. As a result, our simulation runs are often much shorter than required by termination bounds that are computed a priori for a desired level of confidence on a large state space. In comparison to previous algorithms for statistical model checking our method is not only faster in many cases but also requires less information about the system, namely, only the minimum transition probability that occurs in the Markov chain. In addition, our method can be generalised to unbounded quantitative properties such as mean-payoff bounds.

Wild-type monomeric α-synuclein can impair vesicle endocytosis and synaptic fidelity via tubulin polymerization at the calyx of held - Eguchi, Kohgaku; Taoufiq, Zachari; Thorn Seshold, Oliver; Trauner, Dirk; Hasegawa, Masato; Takahashi, Tomoyuki (European Journal of Neuroscience)
α-Synuclein is a presynaptic protein the function of which has yet to be identified, but its neuronal content increases in patients of synucleinopa-thies including Parkinson’s disease. Chronic overexpression of α-synuclein reportedly expresses various phenotypes of synaptic dysfunction, but the primary target of its toxicity has not been determined. To investigate this, we acutely loaded human recombinant α-synuclein or its pathological mutants in their monomeric forms into the calyces of Held presynaptic terminals in slices from auditorily mature and immature rats of either sex. Membrane capacitance measurements revealed significant and specific inhibitory effects of WT monomeric α-synuclein on vesicle endocytosis throughout development. However, the α-synuclein A53T mutant affected vesicle endocytosis only at immature calyces, where as the A30P mutant had no effect throughout. The endocytic impairment by WTα-synuclein was rescued by intraterminal coloading of the microtubule (MT) polymerization blocker nocodazole. Furthermore, it was reversibly rescued by presynaptically loaded photostatin-1, a pho-toswitcheable inhibitor of MT polymerization, inalight-wavelength-dependent manner. Incontrast, endocyticinhibition by the A53T mutant at immature calyces was not rescued by nocodazole. Functionally, presynaptically loaded WT α-synuclein had no effect on basal synaptic transmission evoked at a low frequency, but significantly attenuated exocytosis and impaired the fidelity of neurotransmission during prolonged high-frequency stimulation. We conclude that monomeric WTα-synuclein primarily inhibits vesicle endocytosis via MT overassembly, thereby impairing high-frequency neurotransmission.

Planar matchings for weighted straight skeletons - Biedl, Therese; Huber, Stefan; Palfrader, Peter (International Journal of Computational Geometry and Applications)
We introduce planar matchings on directed pseudo-line arrangements, which yield a planar set of pseudo-line segments such that only matching-partners are adjacent. By translating the planar matching problem into a corresponding stable roommates problem we show that such matchings always exist. Using our new framework, we establish, for the first time, a complete, rigorous definition of weighted straight skeletons, which are based on a so-called wavefront propagation process. We present a generalized and unified approach to treat structural changes in the wavefront that focuses on the restoration of weak planarity by finding planar matchings.

Universality for a class of random band matrices - Bourgade, Paul; Erdös, László; Yau, Horng; Yin, Jun (Advances in Theoretical and Mathematical Physics)
We prove the universality for the eigenvalue gap statistics in the bulk of the spectrum for band matrices, in the regime where the band width is comparable with the dimension of the matrix, W ~ N. All previous results concerning universality of non-Gaussian random matrices are for mean-field models. By relying on a new mean-field reduction technique, we deduce universality from quantum unique ergodicity for band matrices.

Bogoliubov correction to the mean-field dynamics of interacting bosons - Nam, Phan; Napiórkowski, Marcin M (Advances in Theoretical and Mathematical Physics)
We consider the dynamics of a large quantum system of N identical bosons in 3D interacting via a two-body potential of the form N3β-1w(Nβ(x - y)). For fixed 0 = β < 1/3 and large N, we obtain a norm approximation to the many-body evolution in the Nparticle Hilbert space. The leading order behaviour of the dynamics is determined by Hartree theory while the second order is given by Bogoliubov theory.

Single sideband microwave to optical photon conversion-an-electro-optic-realization - Rueda Sanchez, Alfredo R; Sedlmeir, Florian; Collodo, Michele; Vogl, Ulrich; Stiller, Birgit; Schunk, Gerhard; Strekalov, Dmitry; Marquardt, Christoph; Fink, Johannes M; Painter, Oskar; Leuchs, Gerd; Schwefel, Harald (Optics InfoBase Conference Papers)
We present results on nonlinear electro-optical conversion of microwave radiation into the optical telecommunication band with more than 0.1% photon number conversion efficiency with MHz bandwidth, in a crystalline whispering gallery mode resonator

Scattering-aware texture reproduction for 3D printing - Elek, Oskar; Sumin, Denis; Zhang, Ran; Weyrich, Tim; Myszkowski, Karol; Bickel, Bernd; Wilkie, Alexander; Krivanek, Jaroslav (ACM Transactions on Graphics)
Color texture reproduction in 3D printing commonly ignores volumetric light transport (cross-talk) between surface points on a 3D print. Such light diffusion leads to significant blur of details and color bleeding, and is particularly severe for highly translucent resin-based print materials. Given their widely varying scattering properties, this cross-talk between surface points strongly depends on the internal structure of the volume surrounding each surface point. Existing scattering-aware methods use simplified models for light diffusion, and often accept the visual blur as an immutable property of the print medium. In contrast, our work counteracts heterogeneous scattering to obtain the impression of a crisp albedo texture on top of the 3D print, by optimizing for a fully volumetric material distribution that preserves the target appearance. Our method employs an efficient numerical optimizer on top of a general Monte-Carlo simulation of heterogeneous scattering, supported by a practical calibration procedure to obtain scattering parameters from a given set of printer materials. Despite the inherent translucency of the medium, we reproduce detailed surface textures on 3D prints. We evaluate our system using a commercial, five-tone 3D print process and compare against the printer’s native color texturing mode, demonstrating that our method preserves high-frequency features well without having to compromise on color gamut.